Standards and Principles to Enable Interoperability and Integration of 5P Medicine Ecosystems - Blobel, Bernd; Ruotsalainen, Pekka; Giacomini, Mauro (Studies in health technology and informatics, 2022)
Health and social care ecosystems are currently a matter of foundational organizational, methodological and technological paradigm changes towards personalized, preventive, predictive, participative precision (5P) medicine. For designing and implementing such advanced ecosystems, an understanding and correct representation of structure, function and relations of their components is inevitable. To guarantee consistent and conformant processes and outcomes, the specifications and principles must be internationally standardized. Summarizing the first author's Keynotes over the last 15 years of pHealth conferences, the paper discusses concepts, standards and principles of 5P medicine ecosystems including their design and implementation. Furthermore, a guidance to find and to deploy corresponding international standards in practical projects is provided.
Keywords: modeling; ekosystém; 5P medicine; individualizovaná medicína; integration; knowledge management; Precision Medicine; System architecture; ecosystem; Ecosystem; knowledge representation; interoperability